1999
DOI: 10.1093/emboj/18.24.7056
|View full text |Cite
|
Sign up to set email alerts
|

C to U editing of the anticodon of imported mitochondrial tRNATrp allows decoding of the UGA stop codon in Leishmania tarentolae

Abstract: All mitochondrial tRNAs in kinetoplastid protists are encoded in the nucleus and imported into the organelle. The tRNA Trp (CCA) can decode the standard UGG tryptophan codon but can not decode the mitochondrial UGA tryptophan codon. We show that the mitochondrial tRNA Trp undergoes a specific C to U nucleotide modification in the first position of the anticodon, which allows decoding of mitochondrial UGA codons as tryptophan. Functional evidence for the absence of a UGA suppressor tRNA in the cytosol, using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
110
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(112 citation statements)
references
References 55 publications
2
110
0
Order By: Relevance
“…Thus, it is unexpected that trypanosomatids import the tRNA Trp . The way Leishmania mitochondria accommodate the change in the genetic code is by mitochondria-specific C3U editing of the first anticodon position of the imported tRNA Trp (13). In the present work, we have analyzed the situation in the closely related T. brucei and shown that although editing of the imported tRNA Trp is necessary, it is not sufficient to allow decoding of the mitochondrial UGA codons.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Thus, it is unexpected that trypanosomatids import the tRNA Trp . The way Leishmania mitochondria accommodate the change in the genetic code is by mitochondria-specific C3U editing of the first anticodon position of the imported tRNA Trp (13). In the present work, we have analyzed the situation in the closely related T. brucei and shown that although editing of the imported tRNA Trp is necessary, it is not sufficient to allow decoding of the mitochondrial UGA codons.…”
Section: Discussionmentioning
confidence: 85%
“…In most systems, the reassignment of the UGA codon is accommodated by a single mutation in the mitochondrial tRNA Trp gene, which probably requires an adaptation of the mitochondrial TrpRS (3). The situation is different for mitochondria of trypanosomatids because they need (i) a mitochondria-specific tRNA editing enzyme that produces the tRNA Trp UCA (13) and (ii) a separate TrpRS (Tb-TrpRS2) with an extended substrate specificity. The need for a record TrpRS is due to the fact that the C3U editing not only changes the decoding properties of the tRNA Trp but also its identity toward the classic TrpRS (Tb-TrpRS1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The gRNAs provide information for post-transcriptional RNA editing in the form of multiple insertions and deletions of uridine residues into the maxicircle-derived mRNAs (for recent reviews, see 19, 27, 28). The kDNA does not encode tRNA genes, and hence all tRNA molecules must be imported from the cytosol 29, 30 .…”
Section: Mitochondrial Genome Architecture and Gene Contentmentioning
confidence: 99%